2022
DOI: 10.18488/73.v10i3.3061
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Parents' Satisfaction with the Quality of Preschool Educational Services

Abstract: For many researchers, satisfaction is a perennially popular research topic, with satisfaction in education being one of the most prevalent aspects. There are a few previous studies that have looked into the satisfaction of parents and students with their high school and college experiences. However, research on parental satisfaction with preschool education is limited, particularly in Vietnam. The purpose of this study was to determine the factors that influenced parents' satisfaction with their children's pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Improving teachers' quality is considered an important goal focusing on the fundamental and comprehensive renovation of education, including the contingent of preschool teachers. Hoang et al (2022) found that the quality of preschool teachers is one of the factors influencing parental satisfaction and willingness to pay for preschools. Preschool teachers are responsible for taking care of and educating children from 0 to 6 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Improving teachers' quality is considered an important goal focusing on the fundamental and comprehensive renovation of education, including the contingent of preschool teachers. Hoang et al (2022) found that the quality of preschool teachers is one of the factors influencing parental satisfaction and willingness to pay for preschools. Preschool teachers are responsible for taking care of and educating children from 0 to 6 years old.…”
Section: Introductionmentioning
confidence: 99%